A general framework dedicated to computational morphogenesis Part II – Knowledge representation and architecture. (November 2018) - Siregar, Pridi; Julen, Nathalie; Hufnagl, Peter; Mutter, George
Abstract: In our previous paper we introduced morphogenesis and post-embryonic life as arising from cells interacting via coupled chemical, electrical and mechanical processes occurring across multiple organization levels. We reviewed these processes from the perspectives of developmental biology and how they relate to physics-based constitutive equations that are well suited to model intercellular interactions' fields. In this paper we will describe a knowledge representation and architectural design strategy that can organize and encode the biochemical, biological and biophysical data necessary to represent and model the highly specialized and diversified cells that constitute living tissues. Since there are about 200 different types of cells in mammalian tissues, a huge amount of molecular, cellular and tissue data must be accounted for. This data cannot be incorporated in an ad hoc manner but, on the contrary, must be organized according to some sound principles. We give an overview of these principles and describe how they can be incorporated as proper features of a Knowledge Base System (KBS) dedicated to computational morphogenesis (CM).